Study on intermittent faults and electrical continuity - Ahmada, Wakil Syed; Perinpanayagam, Suresh; Jennions, Ian K.; Khan, Samir (Elsevier, 2014)
connector, or incorrect installation during initial manufacture and assembly. Unless such issues are narrowed down to a specific root cause, any corrective actions or troubleshooting will be difficult to carry out, and hence its resolution may not make its way into future designs of the system. This leads to further susceptibility to NFF. Intermittent behaviour is often a clear sign of a partially damaged connector, or a connector undergoing a particular degradation mechanism, with the level of intermittency being further aggravated through process variation of harsh environments and parametric faults. In order to further our understanding of the relationship between degradation, operating conditions, intermittent behaviour within the subject, an experimental investigations have been carried out. This paper is a work in progress paper that illustrates a test regime that has been used to stimulate intermittence in electronic connectors whilst subjected to vibration, using both a traditional oscilloscope and bespoke intermittent fault detection equipment, in order to capture an intermittent signature. The results of these experiments provide an insight into the limitations of test equipment and requirements for future intermittent fault detection techniques.
Keywords: Intermittent Faults; No Fault Found; Fault Diagnosis; Test Equipment